SUN-622 Graves Disease Triggered by Lobectomy for Thyroid Cancer - Woods, Allison (J Endocr Soc, 2019)
Background: The incidence of Hashimoto thyroiditis as well as Graves disease in patients with thyroid cancer has been observed however molecular and pathophysiological basis of this association has only been hypothesized. Cases of new onset severe thyrotoxicosis and Graves ophthalmopathy shortly after lobectomy for thyroid cancer have not been described to our knowledge. Case: The patient is a 46-year-old woman who had a 2.5cm thyroid nodule. Fine needle aspiration showed atypia of undetermined significance and subsequent thyroid genomic classifier test Thyroseq confirmed positive for fusions involving THADA and IGF2BP3. Since THADA positive nodules are usually associated with low risk thyroid carcinoma and non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP), thyroid lobectomy was advised. Prior to surgery the patient had positive thyroid peroxidase antibodies and was treated with low dose levothyroxine only during two pregnancies. Surgical pathology confirmed 2.5 cm NIFTP and 2 foci of papillary thyroid microcarcinoma of 0.5mm and 1mm with the background of chronic lymphocytic thyroiditis (Hashimoto). No further therapy was advised. At 6 weeks after left thyroid lobectomy the patient presented for a follow up clinically euthyroid with thyroid stimulating hormone (TSH) of 3 mcIU/mL. Two weeks after this regular follow up visit she started having severe periorbital swelling, double vision and bulging of her eyes that was followed by shortness of breath, palpitations, anxiety, sweating and weight loss. She presented to emergency room and was found to have suppressed TSH and positive TSI and TBII antibodies with high titer. After stabilization of hyperthyroidism with methimazole completion thyroidectomy was performed on patient request. Surgical pathology of the right thyroid lobe showed scattered papillary hyperplasia, chronic inflammation, focal atrophy and lymphoid follicles. Six weeks after completion thyroidectomy the patient is clinically euthyroid on levothyroxine and with significantly improved ophthalmopathy. TSI and TBII antibodies remain positive and continue to downtrend. Conclusion: As partial thyroidectomy for low-risk thyroid carcinoma is becoming increasingly convenient method of therapy we may encounter more surgically triggered autoimmune thyroid disorders in the future.